DETEKSI CEMARAN BAKTERI KOLIFORM DAN Salmonella sp. PADA TEMPE YANG DIKEMAS DAUN PISANG DI DAERAH SALATIGA - Khanifa Nurul Khaq; Lusiawati Dewi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2016)
ABSTRACTBanana leaves-wrapped tempeh is a traditional food as a conventional base of vegetable protein source. Fermented soybeans into tempeh assisted by fungi kind Rhizopusoligosporus, Rhizopusoryzae and Rhizopusstolonifer. Hygiene is very important in the process of fermentation as it will affect the end result of products. Packaging materials can serve as a protective product, but related to the materials used can be the sources of microbial contaminants in food packaging.For small-scale Tempeh industry in Salatiga area commonly use banana leaves to wrap tempeh.The absence of leaves-wrapped tempeh quality standard made the manufacturers ignore the tempeh processing standard quality. The purpose of this study is to obtain data on the number of coliforms contamination and the presence or absence of Salmonella sp. contamination on banana leaves-wrapped soybean tempeh from manufacturer of production 5-10 kg per day in District of Sidorejo and Tingkir, Salatiga with standar provision of SNI 3144-2015.For the detection of coliform contamination, method used Most probable Number (MPN) series of three tubes with Presumtive Test and Comfirmative Test, as well as the detection of Salmonella sp. with SSA (Salmonella Shigella Agar) specific media. The research result that average sample of manufacturers in Sidorejo and Tingkir District have not met the standard limits of coliform contamination. The highest value of coliform contamination was >1100 APM/g and lowest value was 7 APM/g, while the Salmonella sp. detection in average yield positive result but found one sample showed negative result. Found one sample contaminated with Shigella sp. bacteria.High contamination of coliform and Salmonella was identified obtain from the tools and materials used in manufacturing process, lack of sanitation in manufacture environment, and so the individual as the manufacturer.